The Efffect of Using Diary to Improve Students’ Writing - Iin Ainun Nissa; Sabur, Ambuy; Forsia, Lastry (STAIRS: English Language Education Journal, 2021)
This study aims to determine the effect of using a diary as a medium to improve students’ skills in writing a recount text. This study used quantitative methods using quasi-experimental research with non-equivalent control group design. The samples used in this study were 37 students in the experimental class and 38 students in the control class. Data were collected by conducting pre-test and post-test. This research used non-parametric tests (Wilcoxon) because the data were not normally distributed. Then the result of the hypothesis should be lower than0.05. Based on the result from the hypothesis, the data analysis showed that the value of Asymp.Sig (2-tailed) was 0.000. It can be concluded that the working hypothesis (Ha) is accepted, while the null hypothesis (Ho) is rejected. Also, the mean score of the post-test in the experimental class (which was 76.22) was higher than that of the post-test in the control class (which was 63.39). It means that the use of a diary in writing activities brought benefits to the students’ writing skills. Moreover, the students became more creative, fluent, and enthusiastic in learning and expressing themselves.